Impact of Multifidus Muscle Swelling on C5 Palsy After Cervical Laminoplasty. Issue 1 (1st January 2020) - Usami, Yoshitada; Nakaya, Yoshiharu; Hayama, Sachio; Nakano, Atsushi; Fujishiro, Takashi; Neo, Masashi
Abstract : Study Design: Retrospective radiological analysis Objective: The aim of this study was to identify the effects of posterior cervical muscle swelling on C5 palsy (C5P) by evaluating early postoperative magnetic resonance (MR) images. Summary of Background Data: Cervical laminoplasty is an established technique, but the risk of C5P after surgery has not been fully resolved. Studies have reported that lateral stretching and postoperative swelling of the multifidus muscle may cause stretching of the medial branches and cervical nerves. Methods: A total of 214 C5 nerves of 107 consecutive patients who underwent laminoplasty were examined. We reviewed their demographic and surgical data and radiographic and MR images as parameters, including the axial cross-sectional area (CSA) of the posterior muscles. The patients and C5 nerves were divided into C5P and non-C5P groups. The parameters and changes were compared between the two groups to examine correlations with C5P. Results: In demographic data, age, sex, history of smoking, diabetes mellitus, and preoperative Japanese Orthopedic Association scores were not significantly different between the groups. Only body mass index (BMI) was significantly higher in the C5P group. Regarding the surgical and imaging data, the number of laminoplasty, operative time, decompression trough width, cervical sagittal alignment, preoperative spinal cord rotation, and posterior shift of the spinal cord were not significantly different, but the multifidus CSA change ratio was significantly higher in the C5P group. Multiple logistic regression analyses revealed that the multifidus CSA change ratio and BMI were significant independent factors. Conclusion: Multifidus swelling is associated with C5P, possibly through traction of the C5 nerve via the medial branches of the cervical dorsal rami. The medial branch is the shortest of the dorsal rami and may have the largest effect by traction force. Therefore, a gentle maneuver of the deep posterior muscles during surgery is a potential countermeasure to prevent C5P. Level of Evidence: 3 Abstract : We evaluated early postoperative magnetic resonance images to identify the effects of posterior cervical muscle swelling on C5 palsy. A total of 214 C5 nerves of 107 consecutive patients were examined. The multifidus cross-sectional area change ratio and body mass index were significant independent factors, indicating that multifidus swelling impact C5 palsy onset.